Emotional intelligence on career satisfaction / Siti Fazilah Hamid and Noormala Amir Ishak - Hamid, Siti Fazilah; Amir Ishak, Noormala (Universiti Teknologi MARA Selangor, 2019)
Emotional intelligence (EI) describes the ability, capacity, skill, or self-perceived ability to identify, assess, and manage the emotions of one’s self, of others, and of groups. People who possess a high degree of EI know themselves very well and are also able to sense the emotions of others. They are affable, resilient, and optimistic. There are positive associations between EI and career satisfaction (CS). For example, the literature showed satisfaction with work has demonstrated a considerable impact on success in life and in overall psychological wellbeing. Controlling our emotions and expressing it adequately can make a difference in business. Therefore, this paper reviews the influence of EI on CS. Data were collected using a questionnaire conducted on online entrepreneurs. The data were analyzed using SPSS Version 23 and Structural Equation Modeling (SmartPLS).